Antioxidant, Anti-inflammatory, Antibacterial, and Analgesic Activities and Mechanisms of Quinolines, Indoles and Related Derivatives - Zhang, Shan-Shan; Tan, Qiu-Wan; Guan, Li-Ping (Mini Reviews in Medicinal Chemistry, 2021)
Quinoline, isoquinoline, and indoles are common heterocyclic compounds. They have many biological activities, such as antioxidant, anti-inflammatory, antibacterial, antitumor, anti-virus, anti-rheumatism, immunity regulation, expectorant, and analgesic. Over the past few centuries, traditional natural products have made great contributions to the discovery and development of new therapeutic agents. Many important drugs have been found from these three classes of compounds. In this mini-review, we mainly cover the research progress on antioxidant, anti-inflammatory, antibacterial, analgesic activities of quinoline, isoquinoline, and indole compounds over the past 20 years (2000- 2019). We aim to explore new characteristic groups or structures in the search for active lead compounds and provide a basis for rational drug design.
Keywords: analgesic activity